Beyond textbooks: Culturally responsive English teaching in resource-limited Madurese classrooms - Ach Fauzi; Anita Triastuti; Sudarmaji Sudarmaji (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the implementation of Culturally Responsive Teaching (CRT) in English language instruction within a geographically isolated context—specifically, the Sumenep Archipelago, with a focus on Gili Genting, Indonesia. In such remote settings, English teaching is often constrained by limited material resources and a perceived cultural misalignment with Madurese ethnic learners. Employing a qualitative case study design, this research investigates how CRT strategies are operationalized and what implementation challenges emerge in a senior high school in this region. Data were collected through semi-structured interviews with a single English teacher, selected for her sustained instructional experience in the target community. Interview transcripts were analyzed using thematic analysis. Findings indicate that the teacher strategically integrates Madurese cultural elements—including local folklore, communal values, and environmental artifacts—into English lessons to enhance relevance and learner engagement. While such culturally anchored instruction temporarily increased student participation, this engagement remained largely situational. Persistent challenges included a lack of instructional materials, absence of internet or digital media access, and student resistance rooted in the perceived irrelevance of English to daily life. The study concludes that in remote contexts, CRT manifests primarily through adaptive, interaction-dependent strategies but is severely circumscribed by infrastructural constraints. Critically, student resistance appears to stem more from perceived socio-cultural distance than from general motivational deficits, highlighting the need for systemic, context-sensitive support mechanisms.